Finite Element Modeling of the Behaviors of Concrete-Filled Steel Tube (CFT) Columns at Elevated Temperatures - Van Lanh Le; Chang-Hwan Lee; Robel Wondimu Alemayehu; Min Jae Park (Buildings)
Concrete-filled steel tube (CFT) columns are widely used as structural systems because of their high load-bearing capacity and material efficiency. However, under fire conditions, elevated temperatures degrade the mechanical properties of both steel and concrete. When combined with initial geometric imperfections, these factors significantly affect the load distribution and the fire resistance of the structure. Understanding how material properties and geometric factors change in CFT columns at elevated temperatures is essential for ensuring safe and efficient design. This study used the ASTM E119-88 fire curve to establish the relationship between the surface temperature of the structure and the fire resistance duration of the CFT column. Heat transfer and mechanical analyses of the structure were conducted using ABAQUS 2024 software. A comparison of simulation and experimental data showed that the numerical model was highly accurate. The study also addressed the effects of initial geometric imperfections, considering amplification factors of L/1000 and L/500, and compared the simulation results with the experimental data. The results demonstrated that initial geometric imperfections significantly influenced the fire resistance of the columns. Additionally, this study examined the material properties under high-temperature conditions as specified in the AISC 360-22 standard. The study compared the simulation results with the Eurocode standards and experimental data. The findings suggested that utilizing the material properties specified in the AISC 360-22 standard resulted in more conservative predictions of fire resistance for CFT columns, compared to the Eurocode standards. Furthermore, Appendix 4 of the AISC 360-22 standard was used to calculate the fire resistance rating of the CFT column. These calculations were compared with the simulation and experimental results to evaluate the reliability of using ABAQUS 2024 simulation software.